Rapid laser-induced photochemical conversion of sol-gel precursors to In2O3 layers and their application in thin-film transistors - Dellis,S; Isakov,I; Kalfagiannis,N; Tetzner,K; Anthopoulos,TD; Koutsogeorgis,DC (Journal of Materials Chemistry C, 2017)
We report the development of indium oxide (In2O3) transistors via a singlestep laser-induced photochemical conversion process of a sol-gel metal oxideprecursor. Through careful optimization of the laser annealing conditions wedemonstrated successful conversion of the precursor to In2O3 and its subsequentimplementation in n-channel transistors with electron mobility up to 13 cm2/Vs.Importantly, the process does not require thermal annealing making itcompatible with temperature sensitive materials such as plastic. On the otherhand, the spatial conversion/densification of the sol-gel layer eliminatesadditional process steps associated with semiconductor patterning and hencesignificantly reduces fabrication complexity and cost. Our work demonstratesunambiguously that laser-induced photochemical conversion of sol-gel metaloxide precursors can be rapid and compatible with large-area electronicsmanufacturing.